Recovery of positive electrode active material from spent lithium-ion battery - Widijatmoko, Samuel D (2020)
This thesis aims to design and develop environmentally friendly process by using mineral processing technique in liberating and concentration positive electrode active material. The original contribution to the body of knowledge is related to the unique insights into the selective liberation of lithium-ion battery (LIB) by applying cutting mill and attrition scrubbing aim at concentrating LiCoO2 particles.